Do dental screening and treatments prior to heart valve interventions help prevent prosthetic valve endocarditis? A systematic review - Adriana Jacoba Kouwenberg; G Mensink; MWA Van Geldorp; J Schaap; RG Bentvelsen; JE Bergsma (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
Routine screening for infectious dental foci prior to elective heart valve replacement may help prevent postoperative Prosthetic Valve Endocarditis (PVE), a potentially fatal complication. This systematic review assesses the effect of routine screening for infectious dental foci on the incidence of postoperative PVE. The Cochrane Library, PubMed and EMBASE databases were all searched for relevant primary studies. The GRADE system was used to rate the studies. Three primary studies with a very low level of evidence were included in the review. No significant difference was found between the incidence of PVE in groups with or without routine screening for infectious dental foci prior to heart valve replacement. The results of this review do not support or disprove the need for preoperative screening for infectious dental foci to prevent PVE in patients undergoing heart valve replacement. Further research is necessary.